2013
DOI: 10.1016/j.taap.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of beating parameters in human induced pluripotent stem cells enables quantitative in vitro screening for cardiotoxicity

Abstract: Human induced pluripotent stem cell (iPSC)-derived cardiomyocytes show promise for screening during early drug development. Here, we tested a hypothesis that in vitro assessment of multiple cardiomyocyte physiological parameters enables predictive and mechanistically-interpretable evaluation of cardiotoxicity in a high-throughput format. Human iPSC-derived cardiomyocytes were exposed for 30 minutes or 24 hours to 131 drugs, positive (107) and negative (24) for in vivo cardiotoxicity, in up to 6 concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 28 publications
1
96
0
2
Order By: Relevance
“…Based on the electrochemical activation underlying these changes, high-throughput in vitro assays are being developed to monitor the electrical behavior of either single cells or clusters of primary and pluripotent cell-derived cardiomyocytes. [2][3][4] These high-throughput assays complement traditional lower-throughput patch-clamp electrophysiology, and are complemented by novel genetic tools for imaging calcium transients. 5,6 However, these approaches either require that cardiomyocytes be plated onto specialized materials (e.g., multielectrode arrays, microelectrode arrays [MEAs], or synthetic hydrogels embedded with fluorescent particles to track strain 7 ) or involve genetic manipulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the electrochemical activation underlying these changes, high-throughput in vitro assays are being developed to monitor the electrical behavior of either single cells or clusters of primary and pluripotent cell-derived cardiomyocytes. [2][3][4] These high-throughput assays complement traditional lower-throughput patch-clamp electrophysiology, and are complemented by novel genetic tools for imaging calcium transients. 5,6 However, these approaches either require that cardiomyocytes be plated onto specialized materials (e.g., multielectrode arrays, microelectrode arrays [MEAs], or synthetic hydrogels embedded with fluorescent particles to track strain 7 ) or involve genetic manipulations.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, image-processing tools have been applied in attempts to turn such qualitative observations into quantitative data. 3,[8][9][10] Popular image-processing techniques include edge detection and simple pixel intensity monitoring. 8,10 These techniques require the user to specify regions of interest to monitor, which introduces inherent bias.…”
Section: Introductionmentioning
confidence: 99%
“…These cause differences in each species' tolerance to chemical agents (Price et al, 2008), and might yield false-positive or -negative results when human toxicity is evaluated using experimental animals and cells. Tests using many kinds of known cardioactive compounds have shown that hiPS-CMs are useful for evaluation of pharmacological responsiveness in humans (Sirenko et al, 2013;Khan et al, 2013). Thus, assay systems using hiPS-CMs are likely to provide accurate and efficient screening of candidate drugs.…”
Section: Discussionmentioning
confidence: 99%
“…CMs derived from hiPS cells (hiPS-CMs) are artificially generated source of human tissue, and their potential for use in medical and pharmacological applications has been intensively examined (Funakoshi et al, 2016;Kawamura et al, 2012;Khan et al, 2013;Sirenko et al, 2013). In the pharmacological field, hiPS-CMs have been confirmed to show appropriate responsiveness to known cardioactive compounds (Sirenko et al, 2013), and hiPS-CMs are expected to contribute to efficient screening of candidate drugs (Khan et al, 2013). HiPS-CMs are becoming a powerful tool to evaluate human responses.…”
Section: Introductionmentioning
confidence: 99%
“…Case study e: the aim of the study was to investigate if the in vitro assessment of multiple cardiomyocyte physiological parameters enables predictive and mechanistically interpretable evaluation of cardiotoxicity at high throughput level (Sirenko et al, 2013). Human iPSC-derived cardiomyocytes were exposed for 30 min or 24 h to 131 drugs (incl.…”
Section: Scientific Relevance and Standardization Of The Biological Smentioning
confidence: 99%